Pillcam ESO® is more accurate than clinical scoring systems in risk stratifying emergency room patients with acute upper gastrointestinal bleeding. (May 2013) - Gutkin, Ellen; Shalomov, Albert; Hussain, Syed A.; Kim, Sang H.; Cortes, Rafael; Gray, Sondra; Judeh, Hani; Pollack, Simcha; Rubin, Moshe
Background: Upper gastrointestinal bleeding (UGIB) accounts for 400, 000 hospital admissions in the US each year. Despite advances, mortality rates remain high and are estimated to be 5–10%. Early therapeutic endoscopy is widely recommended as a means of reducing morbidity and mortality. The Rockall and Blatchford scores are clinical scoring systems devised to assist in risk stratifying patients with UGIB. In a prior study we found that rapid live bedside video capsule endoscopy (VCE) utilizing Pillcam ESO ® correctly identified patients with high-risk stigmata of bleeding seen on upper endoscopy. In this study, we compare the accuracy of the Rockall and Blatchford scores with Pillcam ESO ® in predicting high-risk endoscopic stigmata. Methods: Pre-endoscopy Blatchford and Rockall scores were calculated for 25 patients (14 males, 11 females) presenting to the emergency room with acute UGIB. The average patient was 66 years of age. A total of 24 out of 25 patients underwent upper endoscopy within 24 hours. One patient did not undergo endoscopy due to clinical instability. The timing of endoscopy was based on clinical parameters in 12 patients, and on live view VCE with Pillcam ESO ® in the other 13 patients. Positive VCE was defined as red blood, clot or coffee grounds. Mean Rockall and Blatchford scores for all 24 patients were compared to determine potential differences between high- and low-risk patients. Rockall and Blatchford scores were also compared with VCE findings. Results: Of 24 patients, 13 had high-risk stigmata on upper endoscopy. The mean Rockall and Blatchford scores were 3 and 13, respectively. In the 11 patients without stigmata, the mean Rockall and Blatchford scores were 2 and 11, respectively. There was no statistically significant difference between the Blatchford scores of the two groups (95% confidence interval [CI] −5.1 to 1.3; p = 0.22). There was no statistically significant difference between the Rockall scores of the two groups (95% CI −2.3 to 0.3; p = 0.11). In the subgroup of 12 patients who underwent VCE prior to endoscopy, 8/12 had positive findings, which were all confirmed at endoscopy. All 4 patients with negative VCE had no high-risk stigmata at endoscopy. Conclusion: In emergency room patients with acute UGIB, neither the Rockall nor the Blatchford scores were able to differentiate high- and low-risk patients identified at endoscopy. Live view VCE, however, was accurate in predicting high-risk endoscopic stigmata, and may be better suited as a risk stratification tool. Additional studies with a larger cohort will be required to validate these findings.